Pneuma sebagai Dasar Kosmopolitanisme: Mencari Titik Temu dan Pisah Etika Kosmopolitanisme Stoa dan Paulus Dalam Surat Galatia 3:28: Pneuma as the Basis of Cosmopolitanism: Finding Common Ground and Differences between Stoic and Pauline Cosmopolitan Ethics in Galatians 3:28 - Taolin, Remigius; Theo, Yohanes (DISKURSUS - JURNAL FILSAFAT DAN TEOLOGI STF DRIYARKARA, 2025)
This paper examines the discourse between the Apostle Paul and Stoic philosophy, with a focus on the concept of cosmopolitanism rooted in the idea of Pneuma. Rather than determining the direction of influence, the study aims to trace the points of convergence and divergence between these two centers of thought. For the Stoics, Pneuma is the rational spirit that unites all human beings regardless of status, ethnicity, or gender. With a similar vision, Paul interprets Pneuma as the Holy Spirit, which unites all people in Christ by transcending the boundaries of Jewish law and custom. Galatians 3:28 illustrates how Paul adapted the spirit of Hellenistic-Roman cosmopolitanism to affirm the collective identity of “children of God” for all believers. This concept of universal brotherhood is particularly relevant in Indonesia, a country known for its pluralism. Abstrak Tulisan ini mengkaji hubungan intelektual antara Rasul Paulus dan filsafat Stoikisme, dengan fokus pada konsep kosmopolitanisme yang didasari gagasan Pneuma. Studi ini tidak bertujuan menetapkan arah pengaruh, melainkan menelusuri titik temu dan perbedaan prinsip kedua pusat pemikir ini. Bagi Stoa, Pneuma adalah roh rasional yang menyatukan seluruh manusia tanpa membedakan status, etnis, atau gender. Paulus, dengan visi serupa, menafsirkannya sebagai Roh Kudus yang mempersatukan semua orang dalam Kristus, melampaui batas hukum dan adat Yahudi. Ayat Galatia 3:28 menyoroti bagaimana Paulus mengadaptasi semangat kosmopolitanisme Helenis-Romawi untuk menegaskan identitas kolektif “anak Allah” bagi semua orang beriman. Pada akhirnya, gagasan persaudaraan universal ini penting bagi kita di Indonesia dengan ciri pluralitasnya. Kata-kata kunci: Paulus, Stoikisme, Pneuma, Kosmopolitanisme